Longitudinal transcriptomic analysis of the hyperoxia-exposed preterm rabbit as a model of BPD - Boggi, Carlotta; Casiraghi, Nicola; Murgia, Xabier; Parolo, Silvia; Scalera, Enrica; Aquila, Giorgio; Catozzi, Chiara; Salomone, Fabrizio; Stretti, Francesca; Minato, Ilaria; Ravanetti, Francesca; Ragionieri, Luisa; et al. (Frontiers in Pediatrics, 2025)
Bronchopulmonary dysplasia (BPD) is a multifactorial chronic lung disease of premature neonates. BPD development depends on prenatal and postnatal factors that induce inflammation, altering alveolar growth and pulmonary vascular development. Animal models are essential to investigate the precise molecular pathways leading to BPD. The preterm rabbit combines many advantages of small (e.g., rodents) and large BPD models (e.g., preterm lambs and baboons). Preterm rabbits display mild-to-moderate respiratory distress at delivery, which, along with continuous exposure to hyperoxia (95% O2), leads to functional and morphological lung changes resembling a BPD-like phenotype. Nevertheless, the molecular pathways leading to the BPD-like phenotype remain poorly understood. Here, we aimed to characterize the longitudinal gene expression in the lungs of preterm rabbits exposed to 95% O2, on postnatal days 3, 5, and 7. Histological analyses confirmed extensive lung injury and reduced lung development after 7 days of hyperoxia. Longitudinal transcriptomic analysis revealed different expression patterns for several genes and pathways. Over time, extracellular matrix organization and angiogenesis were increasingly downregulated. Apoptosis, RNA processing, and inflammation showed the opposite trend. We also investigated the expression of representative genes of these pathways, whose signatures could aid in developing pharmacological treatments in the context of BPD.